THE HYGIENIC AND ATHLETIC IMPORTANCE OF HEALTH-ENHANCING TYPES OF GYMNASTICS FOR HUMAN HEALTH - Abduraimov Diyorbek Tavakkalovich (Bright Mind Publishing, 2025)
This article discusses the hygienic and athletic significance of health-promoting types of gymnastics. Based on scientific research results, the effectiveness of using gymnastics exercises among various age groups for strengthening health, improving quality of life, reducing stress, restoring posture, and achieving overall well-being is highlighted. Various methods and recommendations in this field are provided.
Keywords: Health, physical education, hygiene, athletic development, morning gymnastics, muscle flexibility, breathing exercises, yoga, pilates, quality of life.